Form and symbol in ancient Egypt - Verwey, Erdmuthe Wilhemina (Rhodes University, Faculty of Humanities, Department of Fine Art, 1968)
From thesis: The Egyptian civilization was regarded by the ancients as the ultimate example of' a morally regulated way of life; their judicious political economy was the admiration of the Elians and both Pythagoras and Plato accepted it as ideal, the former in a small select society and the latter on a larger scale .However a society like this,which is accepted, and acted upon as a completed one, in which everything has been considered, (especially the education of and the habituation to it, to make it second nature), does not take the nature of spirit into consideration, because it is precisely that infinite impulse which acts in contemporary life, and changes its very form. This impulse expressed itself in Egypt in a peculiar way. One would expect that a society, which appears to have been so complete, so fixed in every way, could have no characteristic of its own. Religion, one would expect would have been introduced in the same calm peaceful way, in accordance with the regular order of things. Unlike the Chinese civilisation, where every change is excluded, and the fixedness of character recurs perpetually, this calm order in Egypt was threaded with a spirit full of stirring and urgent impulses. We have here the Oriental Massiveness in combination with the African element. It is a spirit which begins to emerge from the merely natural, without freeing itself from nature. It cannot reach free consciousness of being, it only produces this as a problem: the enigma of its being. One half emerges, the other half is hidden. The buildings of the Egyptians are half below the ground while half rises into the air. The whole country is divided into a Kingdom of life and a Kingdom of death. This, however, is in reality no division, but a unity. The fundamental conception of that which the Egyptians regarded as the essence of being, rested on the fixed character of the natural world - in particular the fixed physical cycle of the Nile and the Sun. These two elements, strictly connected, formed the basis of a very simple and unchanging mode of life. Unchanging, because there is a definite physical cycle which the Nile, in connection with the sun, pursued. The sun rises, reaches its culmination, and then retrogrades. So does the Nile.
Keywords: Signs and symbols -- Egypt